Strain fabric analysis applied to hydrothermal ore deposits emplaced during changing geodynamical conditions (Infiernillo and Las Picazas, San Rafael Massif, Argentina) - Japas, Maria Silvia (2013)
Infiernillo and Las Picazas are two small hydrothermal ore deposits in the northern San Rafael Massif (Argentina). They are genetically linked to the Permian Choiyoi volcanic province which reflects the transition from a convergent plate margin to an extensional regime: Calc-alkaline Early Permian Lower Choiyoi magmatism was syntectonic with transpressional deformation of the San Rafael Orogeny whereas transitional Late Permian Upper Choiyoi sequences were emplaced under a transtensional regime during the Post-San Rafael extension. Infiernillo is a Cu–(Mo) porphyry-type deposit hosted by pyroclastic rocks of the Lower Choiyoi. It consists of a central quartz plug surrounded by a potassic and a phyllic halo, and a set of peripheral polymetallic (Cu–Pb–Zn) veins cropping out close to the alteration zone. The Las Picazas deposit consists of a group of low-sulfidation epithermal galena-bearing veins hosted by Early Palaeozoic meta-sediments. Strain fabric and available 2-D and 3-D kinematic analyses were performed in order to define the relationships between both deposits and the geodynamic scenario. These data reveal that a) porphyry emplacement at Infiernillo occurred during the declination of the San Rafael Orogeny, shortly before the change in stress regime, and b) Las Picazas low sulfidation epithermal veins were emplaced during the subsequent transtensional Post-San Rafael regime. These results prove that each ore deposit is linked to a different stress regime reflecting the change in geodynamical conditions that prevailed during the emplacement of the Choiyoi volcanism. Thus, strain fabric analysis at both ore deposits allows us to confirm that the tectonic regime is a major factor in controlling the mineralization style of hydrothermal ore deposits.